ANALISIS KENAKALAN SISWA DAN IMPLIKASINYA TERHADAP LAYANAN BIMBINGAN KONSELING - Afiatin Nisa (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2018)
This study aims to find out about the Analysis of Student Delinquency and Its Implication on Guidance and Counseling Service of SMA YMIK 2 in South Jakarta. The research method used by writer is qualitative method with descriptive approach, that is by collecting data what is from a symptom of phenomenon that exist when research done. Data and data sources in this study are principals, teachers Guidance and Counseling and students of class X amounted to 60 students, through survey techniques. The research instrument used in this research is documentation, interview and observation. Interviews were conducted with school principals and guidance and counseling teachers and observations were made by observing the school environment and the existence of the school. Data analysis technique is done by collecting data, grouping data, analyzing data and interpreting data that will be concluded to be the result of research. The conclusion of this research is that the Analysis of Student Delinquency and Its Implication on Service Guidance and Counseling SMA YMIK 2 in South Jakarta in the category is good enough.